Work-Life Programs and Employment Continuity in a Single Organization: Understanding from Whole-Life Approach to Career Development - Usman, Asna; Akbar, Waqar; Mansoor, Mehren; Imran, Naila; Khan, Saba (UI Scholars Hub, 2021)
This study examines the effect of work-life programs on employment continuity with a mediating role of work-family enrichment in a single organization using a work-family enrichment model. Consistent with the leader–member exchange theory, this study also examines the moderating role of family-supportive supervisor behavior between work-life programs and work-family enrichment. Data was collected from 218 employees working in the financial sector of Pakistan. Using partial least square structural equation modeling, the study findings suggest that work-life programs have no direct effect on employment continuity; however, the results show an indirect effect of work-life programs on employment continuity through the mediating role of work-family enrichment. Although family-supportive supervisor behavior has a significant impact on work-family enrichment, the findings show that it does not moderate the relationship between work-life programs and work-family enrichment. This study indicates to organizations the various work and nonwork factors that an employee considers while making career decisions, thus encouraging organizations to engage in whole-life approach to career development to retain valuable employees.